Population structure and village youth development planning - Ekawati Sriwahyuni; Sofyan Sjaf; Lukman Hakim; Sampean; Ahmad Aulia Arsyad; Sayyid Al Bahr Maulana; Rajib Gandi; Zessy Ardinal Barlan; Muhammad Iqbal (International Journal of Adolescence and Youth)
It is projected that Indonesia would experience a demographic bonus in 2045, when the country’s population dependency ratio will peak at 53.35%. Studying population structure at the village level is essential in response to projections for Indonesia’s future demographic structure. The aim of this research is to explore youth’s position in the middle-income trap, dependency ratio, and the shifting demographic structure in 15 villages in Gianyar, Bali. Additionally, the study assesses the dependency ratio in rural areas and offers a method for determining the family-based dependency ratio. This study used a mixed methodology, using Data Desa Presisi (DDP). The study’s conclusions show that 15 villages in Gianyar, Bali now have an ageing population structure. These results can offer an overview considering rural village development planning with population structure, focusing the human development perspective as an approach to resolve social and economic issues of youth in Indonesia.